Clinically oriented immune heterogeneity in prostate cancer: emerging targets and strategies - Zhan, MingWei; Zhao, BinBin; Wu, Junjie; Li, Kai; Chen, Yibo; Chen, Haote; Zhao, Lin; Zhu, Jingyu (Frontiers in Immunology, 2026)
Prostate cancer (PCa) has long been viewed as an immunologically “cold” malignancy because immune checkpoint inhibitors (ICIs) show limited benefit in unselected patients, particularly after progression to metastatic castration-resistant PCa (mCRPC) or treatment-related neuroendocrine PCa (NEPC). Single-cell and spatial profiling now reveal immune heterogeneity across patients, between lesions, and along the path from localized disease to metastasis. Primary tumors form mosaics of immune-excluded glands, myeloid-suppressed stromal borders, and focal lymphocyte-rich niches with B-cell aggregates and tertiary lymphoid structures (TLS). TLS-high regions represent an actionable “hot minority” resembling inflamed, ICI-responsive cancers, supporting biomarker-guided neoadjuvant or focal immunotherapy. With dissemination, heterogeneity expands across sites; bone metastases become marrow immune organs dominated by suppressive macrophage/monocyte programs and dysfunctional T cells, often driven by the CCL2–CCR6 axis. Standard therapies remodel these ecosystems, creating inflammatory windows yet fostering adaptive resistance. Mechanistically, myeloid-driven, inflammation-coupled rewiring is central to escape: IL-8/CXCR2 signaling and therapy-induced senescence/SASP recruit and polarize suppressive myeloid cells, reinforcing T-cell exclusion and exhaustion. Variable HLA class I loss and hypoxic or metabolic “functional cold zones” add lesion-specific immune invisibility. Clinically, these insights motivate a heterogeneity-aware framework integrating genomic responder subsets with microenvironmental stratification. Barrier-matched strategies include T-cell redirection (PSMA/STEAP1 engagers, bispecifics, CAR-T) and combinations that heat or modulate myeloid cells. Treating immune heterogeneity as a clinical variable enables durable immunotherapy in PCa.